Desensitization With Imlifidase for HLA-Incompatible Deceased Donor Kidney Transplantation: A Delphi International Expert Consensus - Furian, Lucrezia; Heemann, Uwe; Bengtsson, Mats; Bestard, Oriol; Binet, Isabelle; Böhmig, Georg A.; Boletis, John; Briggs, David; Claas, Frans H. J.; Couzi, Lionel; Cozzi, Emanuele; Crespo, Marta; et al. (Transplant International, 2025)
Highly sensitized (HS) patients in need of kidney transplantation (KTx) typically spend a longer time waiting for compatible kidneys, are unlikely to receive an organ offer and are at increased risk of antibody-mediated rejection. Desensitization using imlifidase, which is more rapid and removes total body IgG to a greater extent than other methods, enables transplantation to occur between HLA-incompatible donor-recipient pairs and allows patients to have greater access to kidney transplantation. However, at the moment the project was launched there was limited data and clinical experience with desensitization in general and imlifidase specifically. Hence, this Delphi methodology was employed to achieve a global view of an international panel of 45 experts (comprising transplant nephrologists, surgeons, and HLA specialists) from 15 countries on different aspects of the management of HS patients undergoing HLA-incompatible KTx from a deceased donor (DD) with imlifidase. This Delphi consensus provides clinical practice guidance on the use of imlifidase in the end-toend management of HS patients undergoing an HLA-incompatible DD KTx and supports centers in the development of guidelines on the utilization and integration of imlifidase in clinical practice.